1984
DOI: 10.1093/ajcn/40.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary thiamin deficiency on intestinal functions in rats

Abstract: The effect of dietary thiamin deficiency has been studied on intestinal functions and chemical composition of brush border membranes in rats. Intestinal uptake of glucose, glycine, alanine, and leucine was significantly stimulated in thiamin deficiency compared to pair-fed control group. Studies with glucose and glycine revealed that stimulation of the absorption process occurs only in the presence of Na+ but not in its absence. Km measured in the presence of 140 mM Na+ for glucose and glycine uptakes was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As we known, no studies have yet been made of the effect of thiamin on Na + , K + ‐ATPase, ALP and γ‐GT activities in fish. However, it has been reported that thiamin deficiency reduced the activity of brush border ALP in rats (Mahmood et al. 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we known, no studies have yet been made of the effect of thiamin on Na + , K + ‐ATPase, ALP and γ‐GT activities in fish. However, it has been reported that thiamin deficiency reduced the activity of brush border ALP in rats (Mahmood et al. 1984).…”
Section: Discussionmentioning
confidence: 99%
“…2007). Thiamin deficiency reduced intestine weight, microvillus membrane protein and the activity of brush border alkaline phosphatase (ALP) in rats (Mahmood et al. 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies show that the consumption of herbal supplements rich in thiaminase during pregnancy (132) or alcohol exposure in utero (133) may predispose a fetus to thiamine deficiency during pregnancy and increased risk for ASD. A study conducted on rat pups nursed by thiamine-deficient dams displayed comparable findings, in which the offspring exhibited behavioral abnormalities consistent with ASD symptoms (134).…”
Section: Pathology Of Thiamine Deficiencymentioning
confidence: 92%
“…Dietary vitamin B 1 is necessary for the utilization of the products of glucose catabolism in the synthesis of fatty acids in fish (Zehra & Khan, 2017). In rats, thiamin deficiency reduced intestine weight, microvillus membrane protein and brush‐border alkaline phosphatase activity (Mahmood et al, 1984). Several studies demonstrated that vitamin B 1 had a beneficial influence on the intestine by increasing digestive enzymes activities and promoting tissue integrity in Jian carp ( Cyprinus carpio var.…”
Section: Introductionmentioning
confidence: 99%